2019
DOI: 10.1186/s13023-019-1155-9
|View full text |Cite
|
Sign up to set email alerts
|

RNASET2-deficient leukoencephalopathy mimicking congenital CMV infection and Aicardi-Goutieres syndrome: a case report with a novel pathogenic variant

Abstract: Background Ribonucleases (RNases) are crucial for degradation of ribosomal RNA (rRNA). RNASET2 as a subtype of RNASEs is a 256 amino acid protein, encoded by RNASET2 gene located on chromosome six. Defective RNASET2 leads to RNASET2 - deficient leukoencephalopathy, a rare autosomal recessive neurogenetic disorder with psychomotor delay as its main clinical symptom. The clinical findings can be similar to congenital cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…However, the triad of leukoencephalopathy, calcifications and cysts is often observed. The older age of our patient and the clinical picture with further genetic testing were crucial for the differential diagnosis [ 8 ]. In Cockayne syndrome, systemic changes, which were absent in our patient, are associated with neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the triad of leukoencephalopathy, calcifications and cysts is often observed. The older age of our patient and the clinical picture with further genetic testing were crucial for the differential diagnosis [ 8 ]. In Cockayne syndrome, systemic changes, which were absent in our patient, are associated with neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of complex I subunits result in numerous clinical presentations including leukodystrophy, optic neuropathy, and encephalopathy (reviewed in [ 41 , 42 ]). Interestingly, leukodystrophy and congenital CMV are difficult to distinguish [ 43 ].…”
Section: Etc and Its Role In Hcmv Replicationmentioning
confidence: 99%
“…A case report performed using brain imaging analysis on a 5-month-old patient with motor delay, neurological regression, infrequent seizures, and microcephaly revealed the presence of white matter abnormalities, calcification, and cysts in the anterior temporal region [ 84 ]. To investigate the underlying cause, the authors performed a screening for mutations in the RNASET2 and RMND1 genes together with a comprehensive review of previously reported cases of individuals with RNASET2-deficient leukodystrophy, comparing their clinical data and magnetic resonance imaging (MRI) with the observation reported in the case report.…”
Section: T2 Rnases: Biological Rolesmentioning
confidence: 99%
“…To investigate the underlying cause, the authors performed a screening for mutations in the RNASET2 and RMND1 genes together with a comprehensive review of previously reported cases of individuals with RNASET2-deficient leukodystrophy, comparing their clinical data and magnetic resonance imaging (MRI) with the observation reported in the case report. Using this analysis, the authors identified a novel homozygous variant of c.233C > A; p.Ser78Ter in exon 4 of the RNASET2 gene compatible with the diagnosis of RNASET2-deficient leukoencephalopathy [ 84 ].…”
Section: T2 Rnases: Biological Rolesmentioning
confidence: 99%